A RHETORICAL STUDY OF THE TENNYSON’S POEMS - Ainur Rohmah (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2016)
A rhetorical study belongs to descriptive research. It was intended to find rhetoric form that consists of figure of thought, rhetorical figure, and imagery in the Alfred Lord Tennyson’s poems In Memoriam. Data reduction or data selection was used to collect the data. Meanwhile, the technique of analyzing data which was used in the research was permutation and repetition technique. The finding shows that the types of figure of thought are simile, metaphor and personification; the types of figure of speech are alliteration, assonance, asyndeton, polysindeton and anastrophe, and the types of imagery are visual, auditory and kinetic imagery.